The Impact of The COVID Pandemic on The Value of Consumer and Mortgage Loans Granted by Polish Banks - Małgorzata Białas; Izabela Emerling (Communications of International Proceedings, 2021)
The pandemic had a major impact on the economic and financial situation of retail customers. In the era of COVID  19, a lot of people temporarily lost their income, which contributed to the search for financing sources in the form of consumer and mortgage loans. The purpose of this article is to analyze whether the pandemic has affected the value and quality of mortgage and consumer loans from banks to households. The main research objective of this article is to investigate and compare the value and types of consumer loans granted in Poland in the years preceding the crisis caused by the pandemic and during COVID 19. The basic research hypothesis is: The COVID  19 crisis contributed to a deterioration in the quality and value of loans granted to households by banks in Poland. The verification of this research hypothesis is the main goal of this article. The applied research methods are based on literature studies and the analysis of numerical data regarding loans granted to individual customers by the bank, such as individual customers. The analysis was carried out on the basis of financial data contained in various reports on the banking sector in Poland in 2018-2021 and available on the Internet.